Managing legal risks associated with intellectual property on the web. (14th January 2008) - Kienle, Holger; German, Daniel; Tilley, Scott; Muller, Hausi
Intellectual Property (IP) has taken a prominent place on the web. Today's organisations need to know the ways in which their websites can be the target of costly IP litigation. Organisations also need to know how to manage and protect their own IP that they expose through their web presence. This paper provides an overview of the legal risks associated with IP on the web. Managing such risks begins with gaining a clear understanding of how to address the salient issues related to IP that any organisation has to take into account when it has a web presence or provides a service using the web. Towards this end, a comprehensive survey of existing IP case law in the context of web content is provided. The survey focuses on three essential IP areas: copyright, patents, and trademarks.